2013
DOI: 10.1523/jneurosci.4741-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

The Hand Sees Visual Periphery Better Than the Eye: Motor-Dependent Visual Motion Analyses

Abstract: Information pertaining to visual motion is used in the brain not only for conscious perception but also for various kinds of motor controls. In contrast to the increasing amount of evidence supporting the dissociation of visual processing for action versus perception, it is less clear whether the analysis of visual input is shared for characterizing various motor outputs, which require different kinds of interactions with environments. Here we show that, in human visuomotor control, motion analysis for quick h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 73 publications
1
16
2
Order By: Relevance
“…Returning to the studies in which the eyes were not pursuing a moving target, we see an apparent discrepancy between the results of our Experiment 3 and those of Gomi, Abekawa and Shimojo [22]. While we found that only motion nearby the targets was important, they showed that adding motion in the periphery made a difference.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Returning to the studies in which the eyes were not pursuing a moving target, we see an apparent discrepancy between the results of our Experiment 3 and those of Gomi, Abekawa and Shimojo [22]. While we found that only motion nearby the targets was important, they showed that adding motion in the periphery made a difference.…”
Section: Discussioncontrasting
confidence: 99%
“…The moving background’s influence was also similar to the influence that was found when moving towards the position at which a target had been flashed [26], and when moving towards the position at which a static target had been just before the movement started [22,23,33,34]. Before discussing the small differences between how the moving background influenced the arm in our interception task and in movements towards static, flashed or removed targets, we will first discuss two larger apparent discrepancies between our results and those of previous studies in which the background moved while the eyes were pursuing a moving target that was to be hit.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Although these results would point to a strong dissociation in visual processing between perception and action, it is unclear whether all actions share a common representation of visual space. A recent study by Gomi, Abekawa, and Shimojo (2013) compared manual and ocular following responses to visual motion and found evidence for a dissociation, suggesting that visual motion processing may be carried out independently for different motor functions. However, this result is based only on reflexive, involuntary movements that are known to have different functional goals: The ocular following response serves to stabilize the image on the retina (Gellman, Carl, & Miles, 1990) whereas reflexive hand movements are used to adjust hand reaching with respect to concurrent body movements (Gomi, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, RDK stimuli can elicit short-latency pursuit eye movements (Schütz et al 2010) and evoke directionally tuned responses in saccade-related lateral intraparietal neurons (Fanini and Assad 2009), showing that the motion signals in RDK stimuli have direct access to the oculomotor system. While visual target signals may have less direct access to arm motor circuits (Kubanek et al 2013), visual motion stimuli can also alter arm movements at short latencies (Saijo et al 2005;Gomi et al 2006Gomi et al , 2013. Therefore, using color as the critical attribute of the decision cues (DCs) has experimental advantages.…”
mentioning
confidence: 99%